2022
DOI: 10.1021/acsomega.2c01801
|View full text |Cite
|
Sign up to set email alerts
|

Identify Functional lncRNAs in Nonalcoholic Fatty Liver Disease by Constructing a ceRNA Network

Abstract: Aim : To identify functional long noncoding RNAs (lncRNAs) by constructing a NAFLD-related lncRNA–miRNA–mRNA network (NLMMN) based on the hypothesis that lncRNAs, as competitive endogenous RNAs (ceRNAs), are able to regulate mRNA functions by competitive binding to shared miRNAs. Methods : The “Limma R package” was used to identify differentially expressed lncRNAs and mRNAs (DElncRNAs and DEmRNAs). The “miRcode online tool” was used to predict the potential interactions betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…79 Recent studies have shown that lncRNAs, particularly NEAT1, can impact the progression and pathogenesis of NAFLD significantly. 80,81 For instance, in a study involving 119 patients with NAFLD, it was found that serum levels of NEAT1 were increased in these patients and positively correlated with disease symptoms. 69 Additionally, Sun et al revealed that the expression levels of NEAT1 and miR-140 are increased in hepatocytes under NAFLD conditions.…”
Section: Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…79 Recent studies have shown that lncRNAs, particularly NEAT1, can impact the progression and pathogenesis of NAFLD significantly. 80,81 For instance, in a study involving 119 patients with NAFLD, it was found that serum levels of NEAT1 were increased in these patients and positively correlated with disease symptoms. 69 Additionally, Sun et al revealed that the expression levels of NEAT1 and miR-140 are increased in hepatocytes under NAFLD conditions.…”
Section: Nafldmentioning
confidence: 99%
“…This disorder is commonly associated with histological changes such as nonalcoholic steatohepatitis, fibrosis, cirrhosis, and in more advanced stages, HCC 79 . Recent studies have shown that lncRNAs, particularly NEAT1, can impact the progression and pathogenesis of NAFLD significantly 80,81 . For instance, in a study involving 119 patients with NAFLD, it was found that serum levels of NEAT1 were increased in these patients and positively correlated with disease symptoms 69 .…”
Section: Lncrna Neat1 Role In the Pathogenesis Of Liver Diseasesmentioning
confidence: 99%